Anti-cancer Drug Delivery Using Metal Organic Frameworks (MOFs) and Ultrasound. - Ibrahim, Mihad (2016)
A Master of Science thesis in Chemical Engineering by Mihad Ibrahim entitled, "Anti-cancer Drug Delivery Using Metal Organic Frameworks (MOFs) and Ultrasound.," submitted in May 2016. Thesis advisor is Dr. Ghaleb Al Husseini and thesis co-advisor is Dr. Rana Sabouni. Soft and hard copy available.